Genotypic Resistance Remains A Concern In Chronic Hepatitis B Patients With High Viral Load After Lamivudine And Adefovir Combination Therapy - Huang M; Zhong J; Lu C; Deng F; Li L; Nong Y; Liang L; Qin H; Deng Y (Dove Medical Press, 2019)
Meijin Huang,1 Jie Zhong,2 Chunlei Lu,1 Fenglian Deng,1 Li Li,1 Yixi Nong,1 Liudan Liang,1 Houji Qin,1 Yibin Deng3 1Department of Infectious Diseases, Affiliated Hospital of Youjiang Nationalities Medical College, Baise City, Guangxi Province, People’s Republic of China; 2Department of Neurology, The First Affiliated Hospital, Guangxi University of Chinese Medicine, Nanning, Guangxi Province, People’s Republic of China; 3Medical Examination Center, Affiliated Hospital of Youjiang Nationalities Medical College, Baise City, Guangxi Province, People’s Republic of ChinaCorrespondence: Houji QinThe Infectious Department of the Affiliated Hospital of Youjiang Nationalities Medical College, Baise City, Guangxi Province, People’s Republic of ChinaEmail houjiqin1964@163.comYibin DengMedical Examination Center of the Affiliated Hospital of Youjiang Nationalities Medical College, Baise City, Guangxi Province, People’s Republic of ChinaTel/fax +86 76-2802090Email dengyb75@163.comAims: Previous studies have shown that baseline high viral load is closely related to treatment response in chronic hepatitis B (CHB). This study was designed to evaluate the differences of treatment responses between de novo lamivudine (LAM) plus adefovir (ADV) combination therapy compared with entecavir monotherapy (ETV).Methods: A total of 185 HBeAg-positive CHB patients with high viral load were enrolled and assigned to the LAM+ADV group (n=90) or ETV group (n=95). Clinical variables are extracted from medical records.Results: No significant differences in baseline variables were found between the two groups before antiviral treatment. After 104 weeks of antiviral therapy, the mean HBV DNA viral load in the LAM+ADV group decreased from 8.01±0.65 log10 copies/mL to 0.41±1.04 log10 copies/mL, compared with 8.04±0.57 log10 copies/mL to 0.57±1.28 log10 copies/mL in the ETV group (P=0.35). The virological response rate of LAM+ADV group was 82.2% (74/90) at 104 weeks of treatment, and 80.0% (76/95) in the ETV group (P=0.70). For HBeAg serological responses, HBeAg loss occurred in 23.3% (21/90) and 17.9% (17/95) in the LAM+ADV group and the ETV group, respectively (P=0.36). HBeAg seroconversion was observed in 15.6% (14/90) and 15.8% (15/95) in the LAM+ADV group and ETV group, respectively (P=0.96). However, after 104 weeks of treatment, genotypic resistance was confirmed in 8 cases in the LAM+ADV group, a proportion of 8.8% (8/90), compared with an absence of genotypic resistance in the ETV group (P=0.003).Conclusion: Both de novo combination therapy of LAM+ADV and ETV monotherapy could effectively inhibit HBV replication in patients with high viral load. However, the rate of genotypic resistance in LAM+ADV treatment remains a concern. For CHB patients with high viral load, ETV treatment may be superior.Keywords: chronic hepatitis B, high viral load, nucleos(t)ide analogs, virologic response